Political Economy From the Perspective of Ibn Khaldun - Moch Bukhori Muslim; Saepullah Saepullah; Any Widayatsari (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2019)
Te political economy encompasses the management of revenues and spending to achieve the social welfare of the community. Hence, development is not solely emphasized economic growth but also equity. Tis article discusses the political economy according to Ibn Khaldun, written in his book, Muqaddimah. Tis study concludes that that political budgets must be carried out in a balanced manner by establishing budget certainty and increasing the discipline in use of the budget. Legislators make laws, referring to the creation of income sources so that the community will be able to meet their needs independently, and thegovernment can gather capabilities to carry out their duties and functions. Ibn Khaldun saw budget management as a means to solve public matters while also factoring the interests of rulers and governments.